Public participation and multi-way communication in virtual space: Building deliberative democracy in the era of communicative plenty - Mahsun, Muhammad; Parmudi, Mochamad; Masrohatun, Masrohatun; Hashim, Shahrin bin (Jurnal Ilmu Dakwah, 2025)
Purpose - This study examines the phenomenon of Lapor Hendi in Semarang city as a communication channel to enhance public participation in the era of internet-based communication to address two key questions: how does citizen participation in virtual spaces through Lapor Hendi contribute to public policy-making and improving public service quality in Semarang City? How does this experience of participation impact deliberative communication and democracy in virtual spaces within Semarang City? Method - To explore these questions, this study uses a qualitative method with a phenomenological approach that prioritises data collection through in-depth interviews, documentation, and analysis of netizens’ communication texts on social media connected to the Lapor Hendi website. Result  - The results showed that the experience of citizen participation with multi-way communication in expressing aspirations and shaping public discourse through Lapor Hendi has successfully introduced public deliberation into the policymaking processes concerning urban spatial development, public goods governance, and public services. Implication - Qualitative study of the Lapor Hendi initiative in Semarang City offers significant insights into how deliberative democracy can be cultivated and developed in virtual spaces within the local Indonesian context. Originality/Value - This study provides an alternative theory to procedural democracy, which is increasingly experiencing a legitimacy crisis and decline, by developing a communication channel in virtual space for building citizen engagement and democratic policies. *** Tujuan - Studi ini mengkaji fenomena Lapor Hendi di Kota Semarang sebagai saluran komunikasi untuk meningkatkan partisipasi publik di era komunikasi berbasis internet guna menjawab dua pertanyaan kunci: bagaimana partisipasi warga dalam ruang virtual melalui Lapor Hendi berkontribusi pada pembentukan kebijakan publik dan peningkatan kualitas layanan publik di Kota Semarang? Bagaimana pengalaman partisipasi ini mempengaruhi komunikasi deliberatif dan demokrasi dalam ruang virtual di Kota Semarang? Metode - Untuk menjawab pertanyaan-pertanyaan ini, penelitian ini menggunakan metode kualitatif dengan pendekatan fenomenologis yang memprioritaskan pengumpulan data melalui wawancara mendalam, dokumentasi, dan analisis teks komunikasi netizen di media sosial yang terhubung dengan situs web Lapor Hendi. Hasil - Hasil penelitian menunjukkan bahwa pengalaman partisipasi warga dengan komunikasi dua arah dalam mengemukakan aspirasi dan membentuk diskursus publik melalui Lapor Hendi telah berhasil memperkenalkan deliberasi publik ke dalam proses pembentukan kebijakan terkait pengembangan ruang kota, tata kelola barang publik, dan layanan publik.  Implikasi - Studi kualitatif tentang inisiatif Lapor Hendi di Kota Semarang memberikan wawasan signifikan tentang bagaimana demokrasi deliberatif dapat dikembangkan dan ditumbuhkan di ruang virtual dalam konteks lokal Indonesia. Orisinalitas/Nilai - Studi ini menawarkan teori alternatif terhadap demokrasi prosedural, yang semakin mengalami krisis legitimasi dan penurunan, dengan mengembangkan saluran komunikasi di ruang virtual untuk membangun keterlibatan warga dan kebijakan demokratis.